Quality of life and sexual health after perineal reconstruction in Fournier gangrene using pedicled anterolateral thigh flaps - Rossi, Severin Alexander; de Schoulepnikoff, Camille; Guillier, David; Raffoul, Wassim; di Summa, Pietro Giovanni (Frontiers in Surgery, 2022)
Objectives To assess long-term sexual outcome and quality of life after perineal reconstruction by pedicled anterolateral thigh (ALT) flaps after Fournier's gangrene. Postoperative surgical outcomes were assessed; quality of life and sexual function were assessed at long term follow-up (>12 months) with 2 scientifically validated questionnaires. Methods We conducted a retrospective analysis of a prospectively maintained database. Long-term sexual function and quality of life were assessed by standardized questionnaires. Descriptive statistics were conducted. Results 8 patients were included in our study, 5 patients responded to quality of life and sexual function analysis. Surgical outcomes were in line with literature: one minor complication (minor dehiscence requiring a skin graft), one major complication (flap loss, requiring a second, contralateral flap) occurred. No reconstructive failure occurred. Average time to complete wound healing was 17 days (SD ±5). Quality of life scores over 70/100 in four out of five categories; social function was rated lowest: patients reported very few residual complaints. Sexual outcome analysis emphasizes the positive impact of the reconstruction. As expected, Fournier's Gangrene heavily affected patient's sexual health. Conclusions Perineal reconstruction with ALT shows excellent quality of life, and good sexual health outcomes. Currently the lack of reliable and relatable data leads to the impossibility to compare different reconstructive procedures. We emphasize that assessing sexual function and quality of life after perineal reconstruction is paramount to weigh reconstructive success.